Compliance fowards iron tablet supplement among pregnant women in Goverment Maternal and Child Clinic in Kinta district, Perak Darul Ridzuan September 1998 - Saerah Shaharudin,; Hanafiah Mohd. Salleh, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Iron supplementation is being widely practiced in Malaysia in our effort to overcome the problem of iron deficiency anemia especially among pregnant women. Despite such intervention the prevalence of iron deficiency anemia still form a significantly serious problem among our pregnant women. It was postulated that this problem might be attributed to the poor compliance among our pregnant women to the taking of iron supplementation pill as hoped. A cross-sectional study was conducted among the pregnant women attending government ANC clinic in the District of Kinta, Perak D.R. in an effort to study the magnitude of non-compliance to iron supplementation program and to identify the factors involved. The study was conducted from 1 st to 20 Sept. 1998 involving 358 pregnant women attending 6 KKIA in Kinta, Perak D.R It was found that the prevalence of non-compliance to iron supplementation are 26% with 3.1% not taking at all the iron supplementation given. Educational status was found to be inversely related to the noncompliance problem ( p <0.05). Non-compliance is higher among the Malays as compared to the non- Malays, those working compared to the housewives, women given the iron supplementation pill as compared to those buying the pill themselves. Mothers not getting adequate information regarding iron supplementation are at a higher risk to non-compliance compared to those given adequate information, mothers observing food taboo during confinement as compared to those not practicing such practice, and all these relationship are statistically significant ( p<0.05). It is hoped that compliance to iron supplementation can be improved through the spread of more information regarding the problems of iron deficiency anemia during pregnancy with emphasis given on more informations regarding the benefits of iron supplementation.